Cessation of dual antiplatelet therapy and cardiovascular events following acute coronary syndrome. Issue 1 (20th July 2018) - Mazlan-Kepli, Wardati; Dawson, Jesse; Berry, Colin; Walters, Matthew
Abstract : Objective: To assess whether cardiovascular events are increased after cessation of dual antiplatelet therapy (DAPT) following acute coronary syndrome (ACS) and to explore predictors for recurrent events after DAPT cessation during long-term follow-up. Methods: We did a retrospective observational cohort study. We included consecutive people with ACS who were discharged from Scottish hospitals between January 2008 and December 2013 and who received DAPT after discharge followed by antiplatelet monotherapy. The rates of cardiovascular events were assessed during each 90-day period of DAPT treatment and 90-day period after stopping DAPT. Cardiovascular events were defined as a composite of death, ACS, transient ischaemic attack or stroke. Cox regression was used to identify predictors of cardiovascular events following DAPT cessation. Results: 1340 patients were included (62% male, mean age 64.9 (13.0) years). Cardiovascular events occurred in 15.7% (n=211) during the DAPT period (mean DAPT duration 175.1 (155.3) days) and in 16.7% (n=188) following DAPT cessation (mean of 2.7 years follow-up). Independent predictors for a cardiovascular event following DAPT cessation were age (HR 1.07; 95% CI 1.05 to 1.08; p<0.001), DAPT duration (HR 0.997; 95% CI 0.995 to 0.998; p<0.001) and having revascularisation therapy during the index admission (HR 0.58; 95% CI 0.39 to 0.85; p=0.005). Conclusions: The rate of cardiovascular events was not significantly increased in the early period post-DAPT cessation compared with later periods in this ACS population. Increasing age, DAPT duration and lack of revascularisation therapy were associated with increased risk of cardiovascular events during long-term follow-up after DAPT cessation.